2015
DOI: 10.1016/j.matchemphys.2015.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and atomic structure of complex defects in Al- and Ga-highly doped ZnO films

Abstract: Artículo de publicación ISIPoint defects in Ga- and Al-doped ZnO thin films are studied by means of first principles electronic structure calculations. Candidate defects are identified to explain recently observed differences in electrical and spectroscopic behavior of both systems. Substitutional doping in Ga-ZnO explain the metallic behavior of the electrical properties. Complexes of interstitial oxygen with substitutional Ga can behave as acceptor and cause partial compensation, as well as gap states below … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Thus, based on the total energy calculations, substitutional doping of Zn by Ga atoms is highly probable. In addition, previous studies revealed that substitutional doping of Ga atom in the wurtzite ZnO is more likely to occur [40,41]. Therefore, in the following we only consider the substitutional doping.…”
Section: Structural Propertiesmentioning
confidence: 99%
“…Thus, based on the total energy calculations, substitutional doping of Zn by Ga atoms is highly probable. In addition, previous studies revealed that substitutional doping of Ga atom in the wurtzite ZnO is more likely to occur [40,41]. Therefore, in the following we only consider the substitutional doping.…”
Section: Structural Propertiesmentioning
confidence: 99%
“…71 It is also known that nonstoichiometric Ga x O y phases can be formed during the sputtering of Ga 2 O 3 lms, leading to a wide range of oxygen substoichiometry 72 and there is also a possibility of forming ZnGa 2 O 4 phase. 73,74 Another possibility is the strong compensation due to the formation of acceptor complexes, such as, (Ga Zn + O i ) and (Al Zn + O i ), [75][76][77] respectively reported in Ga and Al doped ZnO lms, grown under O-rich conditions. A recent X-ray absorption study of reactively sputtered GZO lms from our group 47 has shown that the formation of (Ga Zn + O i ) acceptor complex depends critically on the availability oxygen during sputtering.…”
Section: Discussionmentioning
confidence: 99%
“…The Al atomic size (0.054 nm) is much smaller than that of Zn (0.074 nm), while the Ga atomic size (0.062 nm) and that of Zn atom are close. The Al atoms can be located in either substitutional or octahedral interstitial sites, while the Ga atoms can only be located in substitutional sites [14][15][16]. For high doping concentration, excessive dopants may reside in the interstitial sites or form oxides, which causes a reduction of crystallinity [13,29].…”
Section: Phase Structuresmentioning
confidence: 99%
“…However, the atomic substitution of Al for Zn remains difficult for high doping concentrations due to the difference in ionic radiuses and coordination preference [14]. Reportedly, Al atoms, whose ionic radius is 0.54 Å, can be found in both substitutional and interstitial sites [15]. Ga has an ionic radius of 0.62 Å, which is close to the Zn ionic radius of 0.74 Å [13].…”
Section: Introductionmentioning
confidence: 99%